Liquidity transformation and Eurosystem credit operations - Benjamin Hartung (European Central Bank (ECB), 2024)
Banks in the euro area can generate high-quality liquid assets (HQLA) by borrowing central bank reserves from the Eurosystem against non-HQLA collateral. This paper quantifies the extent of this liquidity transformation and finds that on average EUR 0.92 of net HQLA are generated for each euro of credit provided by the Eurosystem. The paper then identifies intentional liquidity transformation using two novel approaches: The first approach compares the liquidity profile of already pledged vs new collateral, and the second approach compares the liquidity profile of the pool of pledged securities with banks' total eligible securities holdings. Both approaches show that banks use their least liquid assets as collateral first and pledge more liquid assets only at the margin. This intentional liquidity transformation is sizable and accounts for 30-60% of generated HQLA. These results are relevant for calibrating the collateral framework as well as the optimal size and composition of the Eurosystem balance sheet.
Keywords: C23; E52; E58; G28; 330; Liquidity transformation; collateral framework; central bank operational framework; Liquidity Coverage Ratio; reserve demand